KEMAMPUAN SISTEM SARINGAN PASIR-TANAMAN MENURUNKAN NILAI BOD DAN COD AIR TERCEMAR LIMBAH PENCELUPAN - Budiarsa Suyasa, I W.; Dwijani, Wahyu (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 2 No 1)
Colored of clothes has developed as concentrated in Denpasar area. The process has a negative effect because of waste, the resulting organic toxicants and heavy metal into aquatic system. The effect of the pollution including the river, well water and organism that live there. The research of bioremedial effectiveness of herb-sand treatment system on laboratory simulation were studied in Denpasar, from June 2004 to September 2004. For laboratory simulation, the plants were cultured in 25 cm sand bed, in between 5 cm palmfiber of which were in between 10 cm pumicestone for the top and 5 cm gravel for the bottom with surface area of 25 x 50 cm2. The result of treatment system showed that effective for decrease biological oxygen demand compared to those of chemical oxygen demand parameters. The treatment system reduced significantly BOD level respectively to 13,15 for 3 days, 11,19 for 10 days and 5,79 for 20 days with 85,55 – 93,63 effectively. While COD level respectively to 76,68 for 3 days, 61,38 for 10 days and 58,57 for 20 days with 42,78 – 56,50 effectively. Time of treatment for 3, 10 and 20 days showed a little increase of pH from 6,87 to 7,00.
Keywords: bioremedial, treatment, effectively